Effectiveness of the use of immune complex vaccine “Novamune” in the prevention of Gamboro's disease in egg poultry farming - V. V. Marchenko; A. V. Kolechko (Науковий вісник Львівського національного університету ветеринарної медицини та біотехнологій імені С.З. Ґжицького: Серія Ветеринарні науки)
In recent decades, the poultry industry has developed rapidly. Increased demand for higher volumes, better quality and competitive prices led to industrialization, intensification and concentration of production. All this has put significant pressure on animals with genetic potential to achieve higher profits and higher efficiency, which in turn increases the risk of infectious diseases. In addition to disease control, there is pressure on producers to reduce the use of antibiotics and other chemicals, on par with the elimination of pathogens, forcing producers to seek optimal disease control methods. In this context, the principles of biosecurity and vaccination have greatly improved efforts and become important tools for disease control. The vaccine market today is quite broad and includes many vaccines developed on the basis of the latest technologies, such as immune complex vaccines, as well as the largest range of recombinant vector vaccines for poultry. However, all of them have many disadvantages and negative points in practical application, namely: different possibilities of overcoming the level of maternal antibodies (MAT), the need to collect blood serum and conduct laboratory tests to determine the exact day of vaccination, some have a high degree of tissue depletion of the bursa of Fabricius (due to destruction of lymphocytes), low percentage of protection of the bird due to incorrect drinking of the vaccine, etc. Therefore, today specialists face key questions, such as effectiveness against variations of a specific microorganism distributed in different parts of the world; compatibility between vaccines; increasing the resistance or preventing (reducing) the isolation and spread of the pathogen in the environment, which are of crucial importance for reducing the risk of the persistence of the pathogen or preventing the spread of the disease; influence or intervention of passive immunity, advantages of using one category of vaccines over others, etc.